Application of association rules to ball possessions in professional men`s football - Maneiro, R.; Amatria, M.; Losada, J. L.; Jonsson, G. K.; Ardá, A.; Iván-Baragaño, I. (Frontiers in Psychology, 2025)
Introduction: This study represents one of the first attempts to apply association rule mining to the analysis of ball possession in professional men`s football. The goal was to uncover hidden patterns among key tactical variables influencing possession success.